2018
DOI: 10.1111/aje.12496
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional value of feeding on crops: Diets of vervet monkeys in a humanized landscape

Abstract: Anthropogenic influences have dramatically altered the environments with which primates interact. In particular, the introduction of anthropogenic food sources to primate groups has implications for feeding behaviour, social behaviour, activity budgets, demography and life history. While the incorporation of anthropogenic foods can be beneficial to primates in a variety of nutritional ways including increased energetic return, they also carry risks associated with proximity to humans, such as risk of being hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 60 publications
5
29
0
Order By: Relevance
“…We used the same pentagon platform array as previously used in Teichroeb and Aguado () but manipulated the quality, rather than the quantity, of food at the sites available to the monkeys to allow direct comparison with this previous study. We assessed the nutritional composition of the natural diet of the vervet monkeys at Nabugabo and we found it to be low in sodium and relatively low in lipids (Table ; Cancelliere, Chapman, Twinomugisha, & Rothman, ). Sodium is critical in supporting overall maintenance and health in nonhuman primates (Robbins, ), and is typically limited in wild primate diets due to its lack of abundance in wild herbs, leaves, and fruits (Rode, Chapman, Chapman, & McDowell, ; Rothman, Van Soest, & Pell, ).…”
Section: Introductionmentioning
confidence: 99%
“…We used the same pentagon platform array as previously used in Teichroeb and Aguado () but manipulated the quality, rather than the quantity, of food at the sites available to the monkeys to allow direct comparison with this previous study. We assessed the nutritional composition of the natural diet of the vervet monkeys at Nabugabo and we found it to be low in sodium and relatively low in lipids (Table ; Cancelliere, Chapman, Twinomugisha, & Rothman, ). Sodium is critical in supporting overall maintenance and health in nonhuman primates (Robbins, ), and is typically limited in wild primate diets due to its lack of abundance in wild herbs, leaves, and fruits (Rode, Chapman, Chapman, & McDowell, ; Rothman, Van Soest, & Pell, ).…”
Section: Introductionmentioning
confidence: 99%
“…We reported on the nutritional characteristics of both wild and cultivated foods, building on our current understanding of chimpanzee feeding ecology and diet within forest-agricultural mosaics. Nevertheless, knowledge of the nutritional compositions of consumed foods alone do not provide details of how primates balance and prioritize their nutrient intake (Cancelliere et al, 2018;Felton, Felton, Lindenmayer, & Foley, 2009;Garber, Righini, & Kowalewski, 2015;Righini, Garber, & Rothman, 2015). Such information is also important if we are to understand fully the strategies primates employ to meet their nutrient and energetic needs from the surrounding environment .…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining primate feeding ecology within human‐impacted environments have revealed diverse crop‐foraging strategies depending on various factors such as availability, proximity and type of cultivated resources, habitat quality and wild food availability, and perceived risks associated with crop‐foraging (Bryson‐Morrison, Tzanopoulos, Matsuzawa, & Humle, 2017; Hockings, Anderson, & Matsuzawa, 2009; McKinney, 2011; McLennan, 2013; Naughton‐Treves, Treves, Chapman, & Wrangham, 1998; Reynolds, 2005; Strum, 2010). Where crops are fully incorporated into the diets, primates often display changes to activity budget and ranging patterns, spending less time foraging and traveling and more time resting (e.g., Altmann & Muruthi, 1988; Cancelliere, Chapman, Twinomugisha, & Rothman, 2018; Saj, Sicotte, & Paterson, 1999; Strum, 2010; Warren, Higham, MacLarnon, & Ross, 2011). Crop consumption by primates has also been associated with a more effective immune response to parasite infections (e.g., Chapman, Speirs, Gillespie, Holland, & Austad, 2006) and, where crop‐foraging by wildlife is tolerated, a reduction in physiological stress (e.g., Lodge, Ross, Ortmann, & MacLarnon, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations